Expression of Ghrelin Receptor (GHS-R1a) mRNA in Gastric Biopsies of Patients with H. Pylori-Associated Gastritis - Abdul Waheed Iqbal, Abdullah, Muhammad Saeed, Qurat ul Ain Javaid, Muhammad Imran Bajwa, Aisha Qaiser (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Ghrelin, a gastric peptide regulating appetite and mucosal integrity, is modulatedby inflammation, and the functional ghrelin receptor GHS-R1a may be altered in Helicobacter pylori–associated gastritis. This experimental study examined